Aristotle, Eudemian Ethics : Translated into English from the Oxford Edition of 2023, with Introduction, Notes and Appendix - Rowe, Christopher, (Classical Studies E-Books Online, Collection 2025., 2025)
This the first and only translation of the new (2023) Oxford edition of Aristotle's Eudemian Ethics, which like that edition excludes the so-called 'common books'. The main aim of the volume is to bring out the riches concealed beneath the surface of what is generally agreed to be a highly corrupt text; the new edition, based on a fresh collation by Rowe himself of the primary manuscripts, supersedes all previous editions, including the 1991 edition of Walzer and Mingay.